Footprints of Hopi History : Hopihiniwtiput Kukveni'at - Kuwanwisiwma, Leigh J.; Ferguson, T. J. (Thomas John), 1950-; Colwell, Chip (John Stephen), 1975- (Book collections on Project MUSE., 2018)
This book demonstrates how one tribe has significantly advanced knowledge about its past through collaboration with anthropologists and historians--Provided by publisher.